2015
DOI: 10.1007/s00392-015-0846-z
|View full text |Cite
|
Sign up to set email alerts
|

Use and impact of thrombectomy in primary percutaneous coronary intervention for acute myocardial infarction with persistent ST-segment elevation: results of the prospective ALKK PCI-registry

Abstract: The use of thrombectomy in patients with STEMI is heterogenous between hospitals. Overall, there was no impact of thrombectomy on TIMI 3 patency or mortality after PCI. In the subgroup of STEMI patients with TIMI 0 flow before PCI individualized thrombectomy had a positive impact on restoration of normal blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
1
1
0
1
Order By: Relevance
“…A recent meta-analysis of randomised trials reporting mortality as a primary outcome (either all-cause or cardiovascular) similarly concluded that, contrary to the expectations of many interventionalists, TA with PCI does not reduce the rates of death, nor secondary endpoints, such as reinfarction, stent thrombosis or stroke. 19 Furthermore, our data extend registry data from STEMI patients 20,21 to patients with NSTEMI/STEMI.…”
Section: Discussionsupporting
confidence: 62%
“…A recent meta-analysis of randomised trials reporting mortality as a primary outcome (either all-cause or cardiovascular) similarly concluded that, contrary to the expectations of many interventionalists, TA with PCI does not reduce the rates of death, nor secondary endpoints, such as reinfarction, stent thrombosis or stroke. 19 Furthermore, our data extend registry data from STEMI patients 20,21 to patients with NSTEMI/STEMI.…”
Section: Discussionsupporting
confidence: 62%
“…A coronária direita e a artéria descendente anterior foram os principais vasos submetidos à extração de trombo. Em comparação com períodos anteriores, P3 apresentava maior prevalência de trombo visível à angiografia (76,6% vs. 88,8% vs. 92,3%; p<0,001), com queda no uso adjunto de 15 enquanto que no registro europeu Euro Heart Survey PCI Registry, compreendendo dados coletados de 33 países da União Europeia, a utilização do AMT ocorreu em 12,6% das ICP primárias − taxa mais próxima da de nosso registro. 16 A CENIC não foi concebida especificamente para a análise do uso de ATM, e dados relacionados às circunstâncias de seu emprego não foram coletados.…”
Section: Resultsunclassified
“…Initially it was associated with decreased mortality in randomized trials and meta‐analyses . More recently, larger trials , meta‐analyses , and large registries with over 27,000 patients have found no improvement in clinical endpoints with CTA. As a consequence, updated STEMI guidelines downgraded routine CTA in STEMI from a Class IIa recommendation to a Class III recommendation .…”
Section: Discussionmentioning
confidence: 99%